Prehranjevalne navade in telesna aktivnost dijakov primorsko-notranjske regije - Radivo, Manica (Obzornik zdravstvene nege, 2016)
Introduction: Healthy eating and physical activity are the determinants which are inseparably linked to adolescents' health. The aim of the study was (1) to evaluate the nutritional status and dietary habits of the third grade secondary school students in the Primorsko-notranjska region; (2) to study their physical activity habits and (3) to research the relationship between their body mass index (kg/m2) and eating habits. Methods: The study was conducted in the spring of 2015 among the population of the third grade secondary school students in the Primorsko-Notranjska region (n = 166). The participants' average age was 18.2 years. The data were collected through an anonymous questionnaire of the open source application 1KA, consisting of 44 questions. Descriptive and inferential statistical data analysis was conducted using SPSS version 22. Results: The study found that the students do not consume fruit and vegetables on a daily basis (74 % boys and 63 % girls). The overall intake of vegetables (151.3 g boys, 166.7 g girls) and legume (138.2 g boys, 141.8 g girls) is lower than that of fruit (172.4 g boys, 170.9 g girls). Only 5.4 % of girls and 4.5 % of boys meet the fish intake recommendations. The students also do not follow the recommendations as to their physical activity. Discussion and conclusion: Despite the numerous healthy eating policy measures, the students do not adhere to the recommended nutritious diet, including eating enough fruits and vegetables. Vegetables, legumes and fish should be more frequently included in school meals. For promoting physical activity among adolescents, sports should be presented and perceived as a value without competition, available to all the children and adolescents.
Keywords: adolescents; fruit; legumes; mladostniki; nutrition; physical activity; prehrana; sadje; stročnice; telesna aktivnost; vegetables; zelenjava